A fast scheme to calculate electronic couplings between P3HT polymer units using diabatic orbitals for charge transfer dynamics simulations. Issue 2 (12th December 2018) - Yu, Tao; Fabunmi, Florence; Huang, Jingsong; Sumpter, Bobby G.; Jakowski, Jacek
Abstract : We propose a fast and accurate calculation method to compute the electronic couplings between molecular units in a thiophene‐ring‐based polymer chain mimicking a real organic semiconducting polymer, poly(3‐hexylthiophene). Through a unit block diabatization scheme, the method employed minimal number of diabatic orbitals to compute the site energies and electronic couplings, which were validated by comparing with benchmark density functional theory calculations. In addition, by using the obtained electronic couplings, a quantum dynamics simulation was carried out to propagate a hole initially localized in a thiophene‐ring unit of the polymer chain. This work establishes a simple, efficient, and robust means for the simulation of electron or hole transfer processes in organic semiconducting materials, an important capability for study and understanding of the class of organic optoelectronic and photovoltaic materials. © 2018 Wiley Periodicals, Inc. Abstract : This work establishes a simple, and robust means for the simulation of electron or hole transfer processes in organic semiconducting materials, an important capability for study and understanding of the class of organic optoelectronic and photovoltaic materials. Through a unit block diabatization scheme, the method employed a minimal number of diabatic orbitals to compute the site energies and electronic couplings, which were validated by comparing with benchmark density functional theory calculations. A quantum dynamics simulation was carried out to propagate a hole initially localized in a thiophene‐ring unit of the polymer chain.